Optic neuritis: a comprehensive review of current therapies and emerging treatment strategies - Chaitanuwong, Pareena; Moss, Heather E. (Frontiers in Neurology, 2025)
BackgroundOptic neuritis (ON) is an inflammatory condition of the optic nerve that can lead to significant visual impairment. It is often associated with multiple sclerosis (MS) but can also occur in other demyelinating diseases, such as neuromyelitis optica spectrum disorder (NMOSD) and myelin oligodendrocyte glycoprotein antibody disease (MOGAD). Understanding the current therapeutic approaches and emerging treatment strategies is critical for optimizing patient outcomes.ObjectiveThis review provides a focused overview of current therapies for demyelinating optic neuritis associated with MS, NMOSD, and MOGAD. Less common autoimmune optic neuropathies, non-autoimmune causes (e.g., infections) and pediatric optic neuritis are not covered.MethodsA review of the literature was conducted, including clinical trials, observational studies, and expert recommendations on the treatment and management of demyelinating ON. The efficacy, safety, and limitations of various therapeutic modalities were assessed.ResultsHigh-dose intravenous corticosteroids remain the mainstay of acute demyelinating ON treatment, accelerating visual recovery but not altering long-term visual outcomes. Immunomodulatory therapies, such as disease-modifying treatments for MS, play a crucial role in preventing recurrent episodes in demyelinating diseases. Emerging therapies, including re-myelination agents, neuroprotective strategies, and novel immunotherapies, show promise in improving visual prognosis and reducing long-term disability.ConclusionWhile corticosteroids remain the primary treatment for acute demyelinating ON, ongoing research into neuroprotective and re-myelinating therapies offers hope for better visual recovery and long-term management. Future studies should focus on optimizing treatment strategies and exploring novel therapeutics to enhance patient outcomes.